Dual-purpose elemental sulfur for capturing and accelerating biodegradation of petroleum hydrocarbons in anaerobic environment - Qian Zhao; Chengmei Liao; Enli Jiang; Xuejun Yan; Huijuan Su; Lili Tian; Nan Li; Fernanda Leite Lobo; Xin Wang (Water Research X)
Hydrophobic organic pollutants in aqueous environments are challenging to biodegrade due to limited contact between microorganisms, the pollutants and the electron acceptor, particularly under anaerobic or anoxic conditions. Here, we propose a novel strategy that uses inexpensive, dual-function elemental sulfur (S0) to enhance biodegradation. Using petroleum hydrocarbons as the target pollutants, we demonstrated that hydrophobic and nonpolar S° can concentrate hydrocarbons while simultaneously serving as an electron acceptor to enrich hydrocarbon-degrading bacteria. The permeable reactive barrier filled with S0 effectively removed petroleum hydrocarbons. In addition to rapid adsorption, we discovered, for the first time, that petroleum hydrocarbons underwent efficient biodegradation through the reduction of S0. Specifically, n-alkanes were degraded by 80 % to 90 % and polycyclic aromatic hydrocarbons by 40 % to 95 %. These degradation rates were 17 % to 30 % and 26 % to 43 % higher, respectively, compared to those observed without S0. Consecutive subcultures combined with untargeted metabolomics analysis revealed that bacteria capable of dissimilatory sulfur reduction enhanced the fermentation process. These bacteria provided electrons to the metabolic network, which facilitated the mineralization of petroleum hydrocarbons. Our findings highlight the significant potential of S° for removing hydrophobic organic pollutants in oxygen-free environments, demonstrate the feasibility of integrating adsorption, biodegradation, and electron supply to enhance pollutant removal.